Rabies virus in McCoy cell line: Part II – Titration - Nogueira, Yeda L. (1992)
The McCoy cell line has showed high sensivity to rabies virus. This cell line presents cythopatic effect (CPE), when infected with rabies virus. Three strains of rabies virus were tested: CVS, ERA, and PV1 and three street virus were isolated: one from a patient bitten by bat, other from a rabid dog and another from bovine. This cell line was used for virus titration purposes due to the presence of cytophatic effect, two techniques for observation of the CPE were used and were compared to the classical method of intracerebral inoculation in mice.